Periodontal disease and rheumatoid arthritis: a systematic review - Kaur, S; White, S; Bartold, P M (Journal of dental research, 2013)
This systematic review considers the evidence available for a relationship between periodontal disease and rheumatoid arthritis. MEDLINE/PubMed, CINAHL, DOSS, Embase, Scopus, Web of Knowledge, MedNar, and ProQuest Theses and Dissertations were searched from the inception of the database until June 2012 for any quantitative studies that examined the association between periodontal disease and rheumatoid arthritis. Nineteen studies met our inclusion criteria. Good evidence was found to support an association between these conditions with regard to tooth loss, clinical attachment levels, and erythrocyte sedimentation rates. Moderate evidence was noted for C-reactive protein and interleukin-1β. Some evidence for a positive outcome of periodontal treatment on the clinical features of rheumatoid arthritis was noted. These results provide moderate evidence based on biochemical markers and stronger evidence with regard to clinical parameters that common risk factors or common pathologic processes may be responsible for an association between rheumatoid arthritis and periodontal disease. Further studies are required to fully explore both the biochemical processes and clinical relationships between these 2 chronic inflammatory conditions. There is a need to move from case-control studies to more rigorous studies using well-defined populations and well-defined biochemical and clinical outcomes as the primary outcome measures with consideration of potential confounding factors.